Development of an APPLE III undulator prototype with three-dimensional force compensation for SHINE - Yu, Cheng; Zhu, Ya; Zhang, Wei; Yang, Jie; He, Yongzhou; Zhen, Tingting; Liu, Tao; Lei, Yangyang; Yuan, Qibing; Yuan, Dao; Wen, Yongmei; Deng, Rongbing; et al. (Frontiers in Physics, 2023)
The Shanghai High repetition rate XFEL and Extreme light facility (SHINE) plans to install several elliptically polarizing undulators (EPUs) as afterburners behind the plane undulator section to obtain nearly-saturated circularly polarized FEL radiation. Therefore, the SHINE R&D project needs to develop a 4-m-long EPU with an effective magnetic field of 1.5 T, a period of 68 mm and a minimum gap of 3 mm. A magnetic force compensation EPU prototype has recently been built and tested at Shanghai Synchrotron Radiation Facility (SSRF) based on the addition of permanent magnets. This prototype can realize magnetic compensation under various polarization modes in all working gaps, so reducing the deformation of the girders and maintaining sufficient rigidity of the mechanical structure. A girder deformation monitoring system was established to obtain real force compensation feedback. The final magnetic field measurement results meet the physical requirements, the proposed scheme can be used as an alternative to the EPU with a high magnetic field and large magnetic force.